2010
DOI: 10.1375/prp.4.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Sudanese Refugees in Australia: The Impact of Acculturation Stress

Abstract: Refugees from Sudan are the fastest growing community in Australia. Australian mental health professionals have to be prepared to offer services to this ethnic group along with the other mainstream and diverse consumers. In order to offer culturally competent services, these mental health professionals are required to be familiar with this emerging community. As such, a review was undertaken with two main goals. Firstly, the review aimed to educate Australian mental health professionals about the demographics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 43 publications
3
55
0
Order By: Relevance
“…Engall (2011) has also highlighted the need for providing culturally appropriate services for South Sudanese community members and emphasises the need for upgrading cultural literacy among professionals and social workers in the resettlement field. Using literature on refugees, Milner and Khawaja (2010) and Khawaja and Milner (2012) pointed out potential risks associated with the acculturation process for South Sudanese migrants in Australia. Their study found that in attempting acculturation, migrants may face conflicts or pressures in intergenerational relationships, gender roles, and marital relationships according to the stage that each migrant is at in this process (Whitebeach, 2014).…”
Section: Conflicted Adaptation and Acculturation Processesmentioning
confidence: 99%
“…Engall (2011) has also highlighted the need for providing culturally appropriate services for South Sudanese community members and emphasises the need for upgrading cultural literacy among professionals and social workers in the resettlement field. Using literature on refugees, Milner and Khawaja (2010) and Khawaja and Milner (2012) pointed out potential risks associated with the acculturation process for South Sudanese migrants in Australia. Their study found that in attempting acculturation, migrants may face conflicts or pressures in intergenerational relationships, gender roles, and marital relationships according to the stage that each migrant is at in this process (Whitebeach, 2014).…”
Section: Conflicted Adaptation and Acculturation Processesmentioning
confidence: 99%
“…For many students from African refugee backgrounds transition to the mainstream setting is associated with emotional and behavioural problems (Brown, Miller, & Mitchell, 2006;Lloyd, 2006;Milner & Khawaja, 2010;Poppitt & Frey, 2007;Ziaian, Anstiss, Antoniou, Baghurst, & Sawyer, 2012) and subsequent increases in non-conformity and aggressive behaviour (Brown et al, 2006;Gunasekera, Houghton, Glasgow, & Boyle, 2014;Hillier, 2002).…”
Section: A Comparison Of Goal Setting and Reputational Orientations Omentioning
confidence: 99%
“…In the Australian context specifically, it has been shown that difficulty in mastering English to a high degree is associated with a range of psychosocial impacts (see, for example, Khawaja, 2007;Milner and Khawaja, 2010;Stanaway et al, 2010). For example, studies of women who migrated from South America indicate that these migrants and their families felt that English language ability was the key to successfully adapting to their new environment (Amezquita et al, 1995;Aizpurua and Fisher, 2008).…”
Section: Linguistic Isolationmentioning
confidence: 99%
“…Language is central in the ability to obtain employment and participate in education, but the need to shift to English has proven to be a challenge for this community in light of the other challenges of acculturation faced by many of its members. While it is likely that language accommodation will emerge in time, this community faces other, equally pressing issues (Milner and Khawaja, 2010).…”
Section: The Arabic Speaking Community In Melbournementioning
confidence: 99%
See 1 more Smart Citation